Energy Strategy for Sustainable Development of Rural Areas Based on the Analysis of Sustainable Digital Economy - Wang, Zhuonan; Zhao, Yan (Frontiers in Psychology, 2021)
Technology has played a vital role in modifying the lifestyle of individuals and the world as a whole. Economies are emerging in such a way that no one has ever thought. Not only this, but the pattern of energy resources consumption has also been the center of attention for researchers in this decade. China has been one of those economies that have adapted such energy strategies in its industrial regime. The economists and information technology working together have done wonders in digitalizing and sustaining the economies and have led to the achievement of sustainable development goals. The current study has been an effort to understand the role of technology and the availability of affordable energy resources in obtaining a sustainable digital economy with the mediating role of sustainable development. The population of the study was IT professionals and economists. The survey data were collected from 285 respondents selected based on purposive sampling. The software adopted for data analysis was Smart-PLS 3.3.3. The study showed that technology utilization had been an important predictor of sustainable development, hence contributing to a sustainable digital economy. Similarly, low operational cost also moderated the relationship of sustainable development and sustainable digital economy that has been the major focus of developing countries. Moreover, the strategy on cutting down the operation costs to bring it down to the level of affordability is a major challenge for the economies like China that have been among the low production cost. Studies on sustainable digital economy regarding technological use are very limited. Hence, the current study will find many advantages for the economists and IT professionals in the future regarding devising the strategies taking into account the sustainable development goals and the achievement of a sustainable digital economy.